(4a+3)(a-1)=0

Simple and best practice solution for (4a+3)(a-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4a+3)(a-1)=0 equation:


Simplifying
(4a + 3)(a + -1) = 0

Reorder the terms:
(3 + 4a)(a + -1) = 0

Reorder the terms:
(3 + 4a)(-1 + a) = 0

Multiply (3 + 4a) * (-1 + a)
(3(-1 + a) + 4a * (-1 + a)) = 0
((-1 * 3 + a * 3) + 4a * (-1 + a)) = 0
((-3 + 3a) + 4a * (-1 + a)) = 0
(-3 + 3a + (-1 * 4a + a * 4a)) = 0
(-3 + 3a + (-4a + 4a2)) = 0

Combine like terms: 3a + -4a = -1a
(-3 + -1a + 4a2) = 0

Solving
-3 + -1a + 4a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(-3 + -4a)(1 + -1a) = 0

Subproblem 1

Set the factor '(-3 + -4a)' equal to zero and attempt to solve: Simplifying -3 + -4a = 0 Solving -3 + -4a = 0 Move all terms containing a to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -4a = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -4a = 0 + 3 -4a = 0 + 3 Combine like terms: 0 + 3 = 3 -4a = 3 Divide each side by '-4'. a = -0.75 Simplifying a = -0.75

Subproblem 2

Set the factor '(1 + -1a)' equal to zero and attempt to solve: Simplifying 1 + -1a = 0 Solving 1 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1a = 0 + -1 -1a = 0 + -1 Combine like terms: 0 + -1 = -1 -1a = -1 Divide each side by '-1'. a = 1 Simplifying a = 1

Solution

a = {-0.75, 1}

See similar equations:

| 18y=29x-52 | | -16.28=29.3-8.6y | | Y-1=2(x-2/3) | | 3x-(9x+5)=2x-37 | | 8m-20=12+6m | | 8.4y+9.77=-62.47 | | -21.32=3.2x+3 | | 3b^2-2=25 | | 8t+6-7t=6 | | 4x-30=7x-54 | | 6.6+1.7n=2.52 | | 5(2-4r)-3r=4r-287 | | 1.01(1.27)(9-x)=11 | | 4b=2b-1 | | 5.5y-6.1=19.20 | | b=3/4 | | 24(1.5+3)=n | | 8z(squared)=6z(squared)+38 | | x+27.3=8.9 | | m/-10=12=67 | | (7/10)/(5/16) | | 4x-5+2x+15=130 | | 4(3-5p)=9p-278 | | 2b+3=46-4 | | v^2+7=32 | | 4/9=x/11 | | 1.5+3=24 | | x-19=8x+2 | | -4y-15=-2y+5 | | 38(17-5.5x)=13(5x-9)+23.2 | | 24=1.5+3 | | 168*0.8=134 |

Equations solver categories